Rapid translation of clinical guidelines into executable knowledge: A case study of COVID‐19 and online demonstration. Issue 1 (14th July 2020) - Fox, John; Khan, Omar; Curtis, Hywel; Wright, Andrew; Pal, Carla; Cockburn, Neil; Cooper, Jennifer; Chandan, Joht S.; Nirantharakumar, Krishnarajah
Abstract: Introduction: We report a pathfinder study of AI/knowledge engineering methods to rapidly formalise COVID‐19 guidelines into an executable model of decision making and care pathways. The knowledge source for the study was material published by BMJ Best Practice in March 2020. Methods: The PROforma guideline modelling language and OpenClinical.net authoring and publishing platform were used to create a data model for care of COVID‐19 patients together with executable models of rules, decisions and plans that interpret patient data and give personalised care advice. Results: PROforma and OpenClinical.net proved to be an effective combination for rapidly creating the COVID‐19 model; the Pathfinder 1 demonstrator is available for assessment at https://www.openclinical.net/index.php?id=746 . Conclusions: This is believed to be the first use of AI/knowledge engineering methods for disseminating best‐practice in COVID‐19 care. It demonstrates a novel and promising approach to the rapid translation of clinical guidelines into point of care services, and a foundation for rapid learning systems in many areas of healthcare.